Implementation of Adaptive Reading Learning Strategies for Slow Learner Students at Mahira Natural Elementary School, Bengkulu City - Meirita sari; Wiga santri rohinia; Heny Friantary; Hengki Satrisno (CV. Edujavare Publishing, 2026)
This study aims to describe the implementation of adaptive reading learning strategies for slow learner students and identify supporting and inhibiting factors in their implementation at Alam Mahira Elementary School in Bengkulu City. This study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of adaptive reading learning strategies is carried out through individual mentoring, the use of visual media, repetition of material, simplification of material delivery, providing flexible learning time, and providing motivation and positive reinforcement according to the characteristics of slow learner students. Supporting factors in the implementation of this strategy include teacher commitment, the availability of learning media, an inclusive school environment, and collaboration between teachers, schools, and parents. Inhibiting factors include differences in reading ability among students, low student concentration and self-confidence, limited time for teachers to provide individual mentoring, and less than optimal parental involvement in accompanying learning activities at home. Thus, the implementation of adaptive reading learning strategies can support the improvement of slow learner students' reading abilities while realizing a more inclusive, effective, and appropriate learning process for students' needs.